2011
DOI: 10.3390/md9101806
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin, a Marine Carotenoid Present in Brown Seaweeds and Diatoms: Metabolism and Bioactivities Relevant to Human Health

Abstract: The marine carotenoid fucoxanthin can be found in marine brown seaweeds, the macroalgae, and diatoms, the microalgae, and has remarkable biological properties. Numerous studies have shown that fucoxanthin has considerable potential and promising applications in human health. In this article, we review the current available scientific literature regarding the metabolism, safety, and bioactivities of fucoxanthin, including its antioxidant, anti-inflammatory, anticancer, anti-obese, antidiabetic, antiangiogenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
392
1
51

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 648 publications
(480 citation statements)
references
References 98 publications
(215 reference statements)
3
392
1
51
Order By: Relevance
“…Our findings also suggest that the effects of O. aurita intake could be related to a synergistic effect between EPA and other microalgal bioactive compounds, such as pigments, fibers, and phytosterols, which are known to have beneficial effects on human health (Lattimer et al, 2010;Peng et al, 2011).…”
Section: Resultsmentioning
confidence: 76%
“…Our findings also suggest that the effects of O. aurita intake could be related to a synergistic effect between EPA and other microalgal bioactive compounds, such as pigments, fibers, and phytosterols, which are known to have beneficial effects on human health (Lattimer et al, 2010;Peng et al, 2011).…”
Section: Resultsmentioning
confidence: 76%
“…Heo et al (2008) have reported the restorative and protective effects of fucoxanthin against H 2 O 2 induced oxidative stress and associated damage. Ax and fucoxanthin (and its metabolites including FuOH) are known to exert antioxidant effect by scavenging superoxide anion and reducing active intermediates as well as up-regulating the activity of antioxidant enzymes in addition to inhibiting molecules such as NF-κB, NO, COX-2 (Augusti et al 2008;Kim et al 2009, Peng et al 2011). …”
Section: Resultsmentioning
confidence: 99%
“…Среди многих видов Bacillariophyta особый интерес для исследователей представляет Cylindrotheca closterium, поскольку она обладает рядом уникальных свойств. В составе ее фотосинтетического аппарата содер-жание фукоксантина приблизительно равно 78 % общего количества каротиноидов (Peng et al, 2011), что составляет 1,7 % сухой биомассы.…”
Section: Introductionunclassified